PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, KEPERCAYAAN DAN KEAMANAN, KENYAMANAN DAN AKSESIBILITAS, SERTA SOSIAL DAN TREN DIGITAL TERHADAP ADOPSI DIGITAL BANKING OLEH GENERASI MILENIAL DI KOTA MANOKWARI - Iin Ulukyanan, Rosina; Lambi, Manuel; Hammar, Yunus Tekad K.R (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of perceived ease of use, trust and security, convenience and accessibility, and social and digital trends on digital banking adoption among millennials in Manokwari City. The research employed a quantitative descriptive-associative method with multiple linear regression analysis. Data were collected from 150 millennial respondents with digital banking experience using purposive sampling through Likert-scale questionnaires. Results indicate that: (1) perceived ease of use has a positive and significant effect on digital banking adoption (β=0.312; t=4.872; sig=0.000); (2) trust and security has a positive and significant effect (β=0.287; t=4.231; sig=0.000); (3) convenience and accessibility has a positive and significant effect (β=0.198; t=2.876; sig=0.005); (4) social and digital trends has a positive and significant effect (β=0.143; t=2.184; sig=0.031). Simultaneously, all four variables significantly affect digital banking adoption (F=73.842; sig=0.000), with R²=0.672, meaning 67.2% of the variation in digital banking adoption is explained by these variables. Perceived ease of use is the most dominant variable. This research underscores the importance of improving interface usability, strengthening security systems, and enhancing digital literacy to promote broader digital banking adoption in West Papua.